Ultra-strong and low-density nanotubular bulk materials with tunable feature sizes - Biener, Monika M (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.